ANALISIS KEMAMPUAN MEMAHAMI PADANAN KATA BAHASA INDONESIA - Ramadan, Syahru (Kantor Bahasa Provinsi Maluku, 2024)
Abstract This research is prompted by the prevalent use of foreign words in Indonesian language communication in public domains. Actually, many of those words have been assimilated into the Indonesian language as equivalent words. From this standpoint, this study aims to (1) describe the proficiency of Indonesian language users in comprehending Indonesian equivalent terms, (2) describe the rationale behind the utilization of equivalent terms, (3) describe the inclination towards employing equivalent terms, and (4) describe the endeavors to enhance the comprehension of equivalent terms. This research is a qualitative descriptive study that employs the researcher as the primary data collection instrument, assisted by questionnaires. The listening method, specifically the techniques of active listening and note-taking, is employed as a data presentation method in this research. The results of this research show that Indonesian language users have a low understanding of equivalent words. This is evident from the 15 foreign vocabulary words asked for their equivalents, only 5 words were understood by most respondents. In addition, the reason respondents chose equivalent words was that they often heard them from others and read articles or news in the media. Furthermore, most respondents tend to choose and use foreign terms rather than their equivalents in communication. Efforts to develop Indonesian language users' understanding of equivalent words include socializing equivalent words, increasing educators' understanding of equivalent words, and directing public figures and the mass media to intensify the use of equivalent words. Keywords: words, word equivalent, foreign language, Indonesian language user Abstrak Penelitian ini dilatarbelakangi atas fenomena merebaknya kosakata asing dalam komunikasi pengguna bahasa Indonesia di ruang publik. Kosakata tersebut sebenarnya telah banyak diserap ke dalam bahasa Indonesia dalam bentuk padanan kata. Dari hal itu, penelitian ini bertujuan (1) mendeskripsikan kemampuan pengguna bahasa Indonesia dalam memahami padanan kata bahasa Indonesia; (2) mendeskripsikan alasan pemadanan kata; (3) mendeskripsikan kecenderungan penggunaan padanan kata; dan (4) mendeskripsikan upaya pengembangan pemahaman terhadap padanan kata. Penelitian ini berjenis deskriptif kualitatif dengan menjadikan peneliti sebagai instrumen utama dan dibantu oleh angket. Metode simak, khususnya teknik simak cakap dan catat, digunakan sebagai metode penyajian data dalam penelitian ini. Hasil penelitian ini menunjukkan bahwa (1) pemahaman pengguna bahasa Indonesia terhadap padanan kata masih rendah. Dari 15 kosakata asing yang ditanyakan padanan katanya, terdapat 5 kata yang dipahami oleh sebagian besar responden. (2) Alasan para responden dalam memilih padanan kata adalah sering mendengar dari orang lain dan membaca artikel atau berita di media. (3) Sebagian besar responden cenderung memilih dan menggunakan istilah asing daripada padanan katanya dalam berkomunikasi. (4) Adapun upaya mengembangkan pemahaman pengguna bahasa Indonesia terhadap padanan kata adalah menyosialisasikan padanan kata, meningkatkan pemahaman pendidik terhadap padanan kata, dan mengarahkan figur publik dan media massa untuk mengintensifkan penggunaan padanan kata Kata kunci: kosakata, padanan kata, bahasa asing, bahasa Indonesia, pengguna bahasa Indonesia